Five Years Annual Report on Neonatal Diarrheal Outbreaks in Yogyakarta - Purnomo Surjantoro; Soeprapto Soeprapto; Marwoto Marwoto (Indonesian Pediatric Society, 1978)
To prevent the morbidity and mortality of diarrhea in neonatal nursery units, especially in developing oountries, we suggest 3 points to be considered :a) planning of bed capacities according to the need of the surrounding area;b) prompt investigation of the best ratio between babies and nurses to guarantee the best nursing care (Walsh, 1971);c) nurse retraining every 3-6 months.